Association of ACO Shared Savings Success and Serious Illness Spending. Issue 3 (May 2021) - Kaufman, Brystana G.; Anderson, David; Bleser, William K.; Muhlestein, David B.; Smith, Nathan; Clough, Jeffrey; McClellan, Mark B.; Saunders, Robert
Abstract : EXECUTIVE SUMMARY: Accountable care organizations (ACOs) need confidence in their return on investment to implement changes in care delivery that prioritize seriously ill and high-cost Medicare beneficiaries. The objective of this study was to characterize spending on seriously ill beneficiaries in ACOs with Medicare Shared Savings Program (MSSP) contracts and the association of spending with ACO shared savings. The population included Medicare fee-for-service beneficiaries identified with serious illness ( N = 2, 109, 573) using the Medicare Master Beneficiary Summary File for 100% of ACO-attributed beneficiaries linked to MSSP beneficiary files (2014–2016). Lower spending for seriously ill Medicare beneficiaries and risk-bearing contracts in ACOs were associated with achieving ACO shared savings in the MSSP. For most ACOs, the seriously ill contribute approximately half of the spending and constitute 8%–13% of the attributed population. Patient and geographic (county) factors explained $2, 329 of the observed difference in per beneficiary per year spending on seriously ill beneficiaries between high- and low-spending ACOs. The remaining $12, 536 may indicate variation as a result of potentially modifiable factors. Consequently, if 10% of attributed beneficiaries were seriously ill, an ACO that moved from the worst to the best quartile of per capita serious illness spending could realize a reduction of $1, 200 per beneficiary per year for the ACO population overall. Though the prevalence and case mix of seriously ill populations vary across ACOs, this association suggests that care provided for seriously ill patients is an important consideration for ACOs to achieve MSSP shared savings. Abstract : Supplemental Digital Content is available in the text